Public policies in the açai production and trade chain: security and food sovereignty in the amazon and the 2030 agenda - Moraes , Pilar Maria de Oliveira; Mello, Daniel (Seven Editora, 2023)
The acai berry is a fruit that has had expressive growth in its production and commercialization in the last two decades, which is based on the discoveries of its nutritional and functional properties in the human diet. This study had as its guiding question "How is Food Safety organized in the acai commercial chain to contribute to objective 2 of the 2030 Agenda? The objective was to carry out an integrative review of the technical and scientific material published, being organized into three chapters: 1. Public Policies in the Acai Productive and Commercial Chain, 2. Safety and Food Sovereignty in Acai Consumption in the Amazon and 3. Consumption Acai berry and Agenda 2030. The following keywords were used: acai berry; food security; Agenda 2030. The results were presented in two summary tables. The publications brought in their content aspects about changes in the way of production and commercialization to meet the growing demand, as well as the quality of the product for the national and international market. Another point analyzed was the public policies established in this process. There was a lack of public policies for the cold chain in the management of the fruit, given its perishability, making it a critical point of control regarding the quality of the product for local populations dependent on the costs that this treatment generates. It was concluded that to reach objective 2 of the 2030 Agenda, public policies are needed to guarantee the production and consumption of quality açaí for the loco-regional population, but the sustainability of this system in guaranteeing the identity and representation of this food. for this present society and future generations.DOI: https://doi.org/10.56238/devopinterscie-044